2021
DOI: 10.1186/s13018-021-02756-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene correlation network analysis to identify regulatory factors in sciatic nerve injury

Abstract: Background Sciatic nerve injury (SNI), which frequently occurs under the traumatic hip and hip fracture dislocation, induces serious complications such as motor and sensory loss, muscle atrophy, or even disabling. The present work aimed to determine the regulating factors and gene network related to the SNI pathology. Methods Sciatic nerve injury dataset GSE18803 with 24 samples was divided into adult group and neonate group. Weighted gene co-expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Therefore, after fracture healing and nerve repair, skeletal muscle atrophy will affect the quality of life and the effects of rehabilitation. [33][34][35] Based on these, conducting further explorations into the pathogenesis of skeletal muscle atrophy for the clinical treatment of orthopedic diseases is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, after fracture healing and nerve repair, skeletal muscle atrophy will affect the quality of life and the effects of rehabilitation. [33][34][35] Based on these, conducting further explorations into the pathogenesis of skeletal muscle atrophy for the clinical treatment of orthopedic diseases is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Injury severity, clinical outcomes, magnitude of physiological decline, and transfused blood volume only minimally affected these patterns. 3 Interestingly, some studies demonstrated activation of chemokine signaling pathway genes in sciatic nerve injury, 34 traumatic brain injury, 35 and acute and chronic spinal cord injuries. 36 , 37 Notably, most patients (16 of 26 patients) in this study had traumatic brain injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Central sensitization is defined as “an amplification of neural signalling within the central nervous system that elicits pain hypersensitivity” [ 148 ], “increased responsiveness of nociceptive neurons in the central nervous system to their normal or subthreshold afferent input” [ 149 ], or “an augmentation of responsiveness of central neurons to input from unimodal and polymodal receptors” [ 150 ]. Despite this difference, all these definitions agreed on the neurophysiological mechanism of increased response to stimuli in central nervous system neurons responsible for the lower pain thresholds, larger receptive fields, and abnormal pain in response to external stimuli [ 151 155 ]. In addition, patients with central sensitization from NCLBP may also present chronic pain in multiple body areas [ 156 , 157 ].…”
Section: Central Sensitisationmentioning
confidence: 99%